Cone-structured seven-level boost inverter topology for improvising power quality using online monitoring controller scheme for DSTATCOM application - Selvakumar, K.; Palanisamy, R.; Kannan, M.; Selvarajan, S.; Selim, Ali; Kotb, Hossam; Bajaj, Mohit; Kamel, Salah (Frontiers in Energy Research, 2022)
In this article, a seven-level triple-time voltage-boosting topology (8S7L-TTB) is proposed, which has eight switches as the minimum. This topology is used as DSTATCOM to eliminate power-quality issues. In a three-phase four-wire distribution system, specific unpredictable issues have emerged through the increase of unbalanced linear and non-linear loads, which has caused various drawbacks such as voltage imbalance, poor voltage regulation, increased reactive components, and harmonics generation, through which the life period of the system has been minimized, undesirable heating has been produced, and the RMS voltage has been reduced. Hence, it is highly essential to eliminate the issues as mentioned earlier. In this research, a PV-based DSTATCOM is introduced for online-monitoring adaptive Chebyshev neural network controller with triple-boost inverter topology. The three-phase system’s D-Q components, which have been continuously extracted under instant-loading conditions, and the reference magnitude, have been compared through the proposed controller. The error signal is received from the adaptive Chebyshev neural network controller, through which the proposed inverter-switching devices are triggered with multi-carrier pulse width-modulation technique are used to compute the THD of 2.79%. Furthermore, this proposed seven-level inverter and controller have solved the aforementioned problems and maintained the floating capacitor’s voltage nearly as similar as the source voltage in different loading conditions to ensure the efficiency of the system is at 96.82%. To ensure its suitability in real-time, the proposed controller is simulated with MATLAB software and validated through the downscale experimental setup and the results are observed.